Engineering the bioelectronic interface : applications to analyte biosensing and protein detection - Davis, Jason J. (RSC Pub., 2009)
The interfacing of man-made electronics with redox proteins and enzymes not only tells us a great deal about the levels of sophistication active in biology, but also paves the way to using it in derived sensory devices. Some of these have already had a profound impact on both clinical diagnostics and the quality of life enjoyed by those unfortunate enough to live with disease. Though much remains to be learnt about controlling and optimising these interfacial interactions, their potential uses are, if anything, growing. Written by leaders in the field, this is the only book to focus on the gen.